Studi Potensi Pembangkit Listrik Tenaga Bayu (PLTB) di Pantai Teluk Penyu Cilacap Menggunakan Analisis Distribusi Weibull - Ulikaryani Ulikaryani; Agus Santoso; Bayu Aji Girawan; Radhi Ariawan; Unggul Satria Jati; Jenal Sodikin; Ari Kristiningsih (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2026)
The ever-increasing demand for electrical energy drives the utilization of renewable energy as a sustainable alternative source. Wind energy is one such potential renewable energy source. As a region situated on the southern coast of Java, Cilacap Regency possesses relatively stable wind characteristics, making it a promising location for the development of wind power plants. This study aims to analyze the wind energy potential in the Cilacap region using the Weibull distribution. The Weibull method was employed to determine the shape parameter (k) and scale parameter (c) based on wind speed data. The analysis results indicate an average wind speed of 6.225 m/s in the Cilacap region especially Teluk Penyu Beach, with Weibull parameters of k = 2.972 and c = 6.973 m/s. These values ​​reflect wind characteristics that are relatively stable and favorable for the development of small- to medium-scale wind power plants. The calculated wind power density (WPD) indicates that the coastal area of ​​Cilacap is suitable for harnessing wind energy as an alternative energy source.